STUDI LITERATUR: PERAN AUDIT INTERNAL DALAM UPAYA MENCEGAH DAN MENDETEKSI KECURANGAN (FRAUD) - Syifa Aulia Ramadhanti; Ghina Fitri Ariesta Susilo (Bajang Institute, 2022)
This research is a literature review that aims to determine the role of internal audit in preventing and detecting fraud in universities. An effective internal control system is an organization’s best protection against fraud prevention. The role of internal audit is very necessary to detect and prevent fraud in universities. Internal audit must be able to help universities in implementing effective control through evaluation of effectiveness and efficiency as well as encouraging universities to make continuous improvements. Internal audit plays a role in assisting universities in achieving their goals by taking an approach to design, evaluate, and improve risk management, university governance processes, and university control effectiveness. Internal audit at universities also acts as a supervisor to prevent and detect fraudulent acts.